Emotion regulation and resilience in the context of adverse childhood experiences: a scoping review - Lay Phing Goh,; Mahadir Ahmad, (Penerbit Universiti Kebangsaan Malaysia, 2024)
Adverse childhood experiences (ACEs) negatively impact individuals' physical and mental health. Research literature often focuses on the impact of ACEs, with resilience and emotion regulation as protective factors. This scoping review aims to investigate the existing literature on how adverse childhood experiences, emotion regulation, and resilience have been defined, assessed, and studied in the empirical literature. Arksey and O’Malley’s five-stage framework was employed as the scoping review methodology. Searches were carried out in three databases: Web of Science (WOS), PubMed, and SCOPUS. Nine studies from the years 2019 to 2023 were included in the final review. There were inconsistencies in the operational definitions and measures used for ACEs, emotion regulation, and resilience. The reviewed literature reinforces that resilience and emotion regulation serve as protective factors against the impacts of ACEs, emphasizing the need for interventions to promote these skills to counteract the negative effects of ACEs. This review also highlights the importance of focusing on emotion regulation as a crucial component in fostering resilience and addressing the long-term consequences of ACEs. Additionally, it highlights the significance of considering the cultural context within this field of study and the use of culturally sensitive approaches to enhance the relevance and effectiveness of interventions.